Manajemen Evaluasi Kinerja Di Lembaga Bahasa LIA Cibinong: Perspektif Penulis - Rhinomuraena Murtoaji Abikusno; Sri Sundari; Marisi Pakpahan (Pusat Riset dan Inovasi Nasional, 2024)
This article discusses the performance evaluation process at the LIA Cibinong Language Institute, which is a crucial step in measuring and assessing employee performance. This process is essential to ensure the effectiveness and efficiency of organizational operations, while providing feedback that supports overall performance improvement. LIA Cibinong, as an educational entity, considers performance evaluation management important in monitoring employee achievements. The evaluation process at LIA Cibinong consists of planning, implementation, assessment, and follow-up. The planning stage establishes the objectives of the performance evaluation in line with the objectives of the organization, with criteria that include quantity, quality, timeliness, and collaboration. Implementation involves collecting performance data through self-assessment, supervisors, and colleagues. The assessment stage uses techniques such as rating scales, comparisons, and free assessments, tailored to the evaluation criteria. Ultimately, the follow-up stage uses the assessment results as feedback, not just evaluation, but as a guide to improving employee performance. Careful implementation of performance evaluation by LIA Cibinong ensures that employees contribute optimally in accordance with the vision and mission of the organization. This process is not only an evaluative instrument, but also a foundation for individual development and overall institutional performance improvement.